Effect of the Confining Pressure on the Dynamic Compression Properties of Transversely Isotropic Rocks - Xuefeng Ou; Xuemin Zhang; Han Feng; Cong Zhang; Junsheng Yang (Advances in Civil Engineering, 2019)
The dynamic compression properties of transversely isotropic rocks and their dependence on the confining pressure and bedding directivity are important in deep underground engineering activities. In this study, a slate is characterized using a split Hopkinson pressure bar (SHPB) test. Five groups of samples with preferred bedding directions (dip angles of 0°, 30°, 45°, 60°, and 90°) are subjected to coupled axial impact loading (low, medium, and high) under confining pressure (0, 5, and 10 MPa). The failure mode, dynamic strength, and Young’s modulus are investigated. The test results show that the tensile splitting effect is significant when there is no confining pressure. However, under a confining pressure (5 and 10 MPa) condition, the cracks that develop along the loading direction can be significantly constrained and the samples are forced to fail along the bedding plane. With increasing confining pressure, the critical dynamic strength significantly increases, and Young’s modulus increases when θ≥45° while it decreases when θ≤30°.